A Knight of Another Sort : Prohibition Days and Charlie Birger, Second Edition - DeNeal, Gary, 1944- (Book collections on Project MUSE., 1998)
"Charlie Birger's legacy is that of the most popular and, arguably, the most violent gangster in southern Illinois during the 1920s. A Russian immigrant who first proved his grit on the streets of St. Louis as a newsboy, Birger later excelled in boxing and breaking horses in the West. But the coming of Prohibition to the coal fields of southern Illinois provided the opportunity for Birger to become a key figure in a maelstrom of violence that would shock the country. Bolstered by years of research and interviews, Gary DeNeal tenders an insightful biography of this controversial character. Enhanced by newly discovered photographs and a new chapter, the second edition of A Knight of Another Sort brings Birger and his bloody era vividly to life." "Drawing from the colorful cast of the living, the dead, and the soon-to-be-dead - a state shared by many associated with Charlie and his enemies, the Shelton gang - DeNeal re-creates Prohibition-era southern Illinois. He depicts the fatal shootout between S. Glenn Young and Ora Thomas, the battle on the Herrin Masonic Temple lawn in which six were slain and the Ku Klux Klan crushed, and the wounding of Williamson County state's attorney Arlie O. Boswell." "The gang wars ended with massive arrests, trials, and convictions of gangsters who once had seemed invincible. Charlie Birger was convicted of the murder of West City mayor Joe Adams and sentenced to death. On April 19, 1928, Birger stood on the gallows looking down on the large crowd that had come to see him die. "It's a beautiful world," Birger said softly as he prepared to leave it."--Jacket.